Peran Orang Tua dalam Membina Moralitas Remaja Putus Sekolah di Kelurahan Fatukbot, Nusa Tenggara Timur - Megarini Tafui (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
This study aims to determine the role of parents in fostering the morality of dropout adolescents, and the inhibiting factors of parents in fostering the morality of dropout adolescents in Fatukbot Village, South Atambua District, East Nusa Tenggara. This type of research uses qualitative methods. The subjects in this study were parents, children, religious leaders and village government. Data collection techniques in this study, namely through observation techniques, interviews, documentation and data analysis techniques used consisted of data reduction, data presentation and conclusions. This research found that the role of parents in fostering the morality of dropout adolescents has been running, but not optimal, so that many teenagers are worried that they do not know what is good and what is bad. The inhibiting factors that cause the role of parents to not run optimally are due to the educational background of the parents, the economic level of the parents, the type of work the parents do and the time available.